Islamic Education 4.0: Integration of Moral Education Values in the Learning Process - Muhlis; Munir Yusuf; Kaharuddin (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2023)
In the Industrial Revolution 4.0 era, humans are required to be able to seek education that is in line with the needs of the time. This is a challenge for Islamic educational institutions in particular, which are often trapped in the dichotomy of religious and general knowledge. Negative stigma still often comes from people who question the lack of scientific integration in Islamic educational institutions, so that they are less adaptive in responding to market needs. This study aims to describe the integration of moral education values into the learning process at Madrasah Aliyah DDI Masamba. This research is qualitative, using normative theological and phenomenological approaches to obtain research data. The results of the study show that, on the one hand, MA DDI Masamba has responded to the industrial era 4.0 by integrating moral education values into the entire learning process. However, on the other hand, the integration process is hampered because the teaching staff has not optimally exemplified morals in the learning process. For this reason, alternative curriculum improvements and follow-up evaluations are needed to develop an integrated and global-minded moral education.